The Music Composition Tajen Jangkrik | Komposisi Musik Tajen Jangkrik - I Wayan Srutha Wiguna; I Komang Sudirga (GHURNITA: Jurnal Seni Karawitan, 2022)
Tajen Jangkrik consists of two words, namely tajen which means fight, and cricket is a small insect with a loud sound. Tajen Jangkrik is a Balinese musical art work that describes the process of playing cricket fighting games. This work raises the phenomenon of youth and old people in Bali past or present, especially in Kesiman Village who play cricket fights for gambling or betting. This work will be realized in the form of innovative musical works using the media, namely Gamelan Semarandana and Gamelan Selonding. The purpose of the creation of this work is as a criticism through Balinese musical works of art to the public that this gambling game is not good to do, it can harm oneself because of betting and harm the living things that are used as a means of playing. The method used in the process of creating works is the creation method of Alma M. Hawkins with three stages in it, namely the exploration stage, the improvisation stage and the forming stage. The recommendation that can be given is how the stylist combines two gamelan barungan with different techniques, materials and characteristics into one complete work. From these recommendations, hopefully it can be an inspiration as a reference for future works.